JAK/STAT signaling in insect innate immunity. Issue 8 (29th July 2019) - Bang, In Seok
Abstract: Lack of an adaptive strategy to combat infection creates opportunities for the innate immune system to guide invertebrate defense mechanisms. The innate immunity signaling cascades in invertebrates are elaborate, complex, and pathogen‐specific. Among invertebrates, the most extended repertoire of molecules that function in the regulatory signaling pathways has been observed in insects. This is highlighted by the fact that antimicrobial peptide (AMP) production against pathogens is orchestrated through diverse immune pathways, either independently or through cross‐talk mechanisms. The Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway coordinates immune responses from cytokines and regulates multiple homeostasis mechanisms in the host. That pathway has been implicated in the regulation of cell growth, differentiation, apoptosis, and inflammatory reactions. Many novel therapeutic interventions for tumors have been aimed at inhibitors of the JAK/STAT cascade. The regulatory pathway has much fewer components in Drosophila, and human homologs of almost all the critical pathway components and negative regulators have been identified. Loss‐of‐function mutation analysis and RNA interference‐based gene silencing modeling have produced functional characterization of the core components and negative regulators in Drosophila melanogaster, Aedes aegypti, and Anopheles gambiae, and in some hymenopteran and lepidopteran species. The genome‐wide analysis of the coleopteran species, Tribolium castaneum and Tenebrio molitor have been explored for elucidation of their JAK/STAT pathway regulatory components. Considering the promise of the JAK/STAT pathway in the mammalian model, the regulatory pathway in insects seems interesting especially for understanding pathogen surveillance mechanisms.